Morpho-Genetic Variability in Phytochemical Composition and Essential Oils of Three Common Lavandula Species Cultivated in Van, Türkiye - Nohutcu, Lutfi; Tuncturk, Murat; Tuncturk, Ruveyde; Selem, Ezelhan (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Lavandula sp. is a valuable plant species as ornamental plant with beautiful inflorescence and aromatic plant with high yield of essential oil. Lavender is mostly produced in Europe, the Middle East, Asia, Northern Africa, France and Bulgaria. Most varieties of lavender are known for their sedative properties and have historically been used to treat diabetes, depression and headaches. Chemical composition and the existence of phenolic compounds may be related to these biological properties. Aim: This study aims to compare morpho-genetic variability in total phenolics, flavonoids, antioxidants and essential oils of three Lavandula species cultivated under identical conditions. As a result of the study, total ash, dry matter, phenolic profile and mineral content of both leaf and inflorescence is clarified. Results: Both inflorescence and leaves L. intermedia has highest flavonoid content value (8.76 and 11.26 mg QE/100 g) for the study. Total antioxidant activity ranged for inflorescence 83.92 to 167.94 μmol TE/g and 75.64 to 135.48 μmol TE/g for leaves. Total phenolic content value (198.29 and 208.92 mg GAE/g) for both inflorescence and leaves obtained from L. dentata. Essential oil yield (v/w) of L. angustifolia found 7.31%, L. intermedia 4.92% and L. dentata 3.92%. Linalool were the predominant essential oil constituents in both L. angustifolia (50.04%) and L. intermedia (48.69%), whereas 1,8-cineole were (82.66%) major constituents in L. dentata. Conclusion: L. angustifolia were more productive in terms of essential oil content and also mineral content for some elements except heavy metals. For phenolic compound, while L. dentata shows higher results with total flavonoid and phenolic content, L. intermedia shows greater total antioxidant activity.
Keywords: Antioxidant Activity; Essential Oils; Lavandula; Mineral Content; Phytochemicals.